THE INFLUENCE OF LIFESTYLE AND CULTURAL TRADITION ON TEGAL CITY COMMUNITY - Tri Mulyani Kartini; Etty Zuliawati Zed (Jurnal Ekonomi, 2023)
This research was conducted to examine the influence of lifestyle and cultural traditions on the people of Tegal City. The population in this study were residents of the city of Tegal, amounting to 70 people. This study uses a quantitative approach, the data for this study were obtained through questionnaires that had been filled out by residents of the city of Tegal, namely a number of 70 respondents. The data analysis method used is the SPSS method of multiple linear regression. This study examines three variables, namely: lifestyle (X1), cultural traditions (X2) as the independent variable and society (Y) as the dependent variable. The results show that lifestyle and cultural traditions have a significant effect on the people of the city of Tegal .